2019
DOI: 10.1016/j.clon.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Experiences, Information Needs, Pain and Quality of Life in Men with Metastatic Castrate-resistant Prostate Cancer: Results from the EXTREQOL Study

Abstract: Delaying progression, ameliorating symptoms and maintaining Quality of Life (QoL) are primary aims of treatment for metastatic Castrate Resistant Prostate Cancer (mCRPC). Real world rather than clinical trial data about symptoms and side effects are sparse. In EXTREQOL patients' QoL, pain and information needs were recorded during treatment. Methods Men with mCRPC from 20 UK cancer centres commencing various systemic mCRPC treatments completed QoL, pain and information needs questionnaires at baseline, 3 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…Patients who managed to have a pain management discussion were in the main satisfied; however, some attributed their pain to their older age, or to conditions other than cancer, for example arthritis, or an activity like gardening. Evidence from the Brief Pain Inventory data for the whole EXTREQOL study sample showed only 39% (22/57) of those with moderate/severe pain experienced ≥ 70% pain relief from their analgesia, and these proportions dropped to 37.5% (15/40) and 36.5% (15/41) at 3 & 6 months follow‐up respectively (Jenkins et al, ). The overall picture from EXTREQOL and other studies is one of less than optimal pain management in this group of men.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who managed to have a pain management discussion were in the main satisfied; however, some attributed their pain to their older age, or to conditions other than cancer, for example arthritis, or an activity like gardening. Evidence from the Brief Pain Inventory data for the whole EXTREQOL study sample showed only 39% (22/57) of those with moderate/severe pain experienced ≥ 70% pain relief from their analgesia, and these proportions dropped to 37.5% (15/40) and 36.5% (15/41) at 3 & 6 months follow‐up respectively (Jenkins et al, ). The overall picture from EXTREQOL and other studies is one of less than optimal pain management in this group of men.…”
Section: Discussionmentioning
confidence: 99%
“…When men are facing life-prolonging treatments, it is, therefore, important to consider and discuss both the benefits and possible harmful effects of the treatments when communicating with the patient (Winkler et al, 2012;Haun et al, 2017). In a recent study, men with mCRPC reported lacking enough information on how the treatment might affect them and their life situation and also on how to access supportive resources (Jenkins et al, 2019). A majority of the men in the present study received chemotherapy as their first life-prolonging treatment but all types of treatments the men received require regular follow-ups and treatment evaluation, something that is commonly handled by contact nurses at the oncology clinics in the Swedish context.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the needs and experiences of men with PC ranging from localized disease to an advanced, palliative phase highlights the men's need for information about treatment options as well as the expected severity and duration of side effects (King et al, 2015). Still, it has been shown that men with mCRPC lack enough information about the treatments and their possible impact of them on their life (Jenkins et al, 2019). Further, QoL has been shown to be more important to men with mCRPC than extending life expectancy with the risk of experiencing debilitating treatment complications (Jones et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being a surrogate endpoint for mortality, metastatic disease is an important clinical outcome in its own right due to the adverse impact on quality of life of the disease and its treatments, whether the metastases are present at diagnosis or occur later through progression. 8,9 ERSPC analyzed rates of total metastatic disease (metastases at diagnosis plus metastatic progression) by arm in a subset of its centers and showed a reduction similar to, but slightly larger than, the reduction in prostate cancer mortality in the trial. 10 The CAP trial reported only on metastatic disease at diagnosis (M1), which was grouped together with N1 and T4 disease, and showed a statistically significant reduction in T4, N1, or M1 disease in the screening arm versus the control arm.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] One of these trials, the European Randomized Study of Screening for Prostate Cancer (ERSPC), found a significant reduction in prostate cancer mortality. 8,9 ERSPC analyzed rates of total metastatic disease (metastases at diagnosis plus metastatic progression) by arm in a subset of its centers and showed a reduction similar to, but slightly larger than, the reduction in prostate cancer mortality in the trial. [3][4][5][6][7] An important additional goal of PSA screening is reducing the rate of metastatic prostate cancer, and this was a secondary endpoint of the screening trials.…”
Section: Introductionmentioning
confidence: 99%